Analysis of anti-SARS-CoV-2 Omicron-neutralizing antibody titers in different vaccinated and unvaccinated convalescent plasma sources - Sullivan, David J.; Franchini, Massimo; Joyner, Michael J.; Casadevall, Arturo; Focosi, Daniele (Nature communications, 2022)
The latest SARS-CoV-2 variant of concern Omicron, with its immune escape from therapeutic anti-Spike monoclonal antibodies and WA-1 vaccine-elicited sera, demonstrates the continued relevance of COVID-19 convalescent plasma (CCP) therapies. Lessons learnt from previous usage of CCP suggests focusing on early outpatients and immunocompromised recipients, with high neutralizing antibody titer units. Here, we systematically review Omicron-neutralizing plasma activity data, and report that approximately 47% (424/902) of CCP samples from unvaccinated pre-Omicron donors neutralizes Omicron BA.1 with a very low geometric mean of geometric mean titers for 50% neutralization GM(GMT 50 ) of ~13, representing a > 20-fold reduction from WA-1 neutralization. Non-convalescent subjects who had received two doses of mRNA vaccines had a GM(GMT50) for Omicron BA.1 neutralization of ~27. However, plasma from vaccinees recovering from either previous pre-Omicron variants of concern infection, Omicron BA.1 infection, or third-dose uninfected vaccinees was nearly 100% neutralizing against Omicron BA.1, BA.2 and BA.4/5 with GM(GMT( 50 )) all over 189, 10 times higher than pre-Omicron CCP. Fully vaccinated and post-BA.1 plasma (Vax-CCP) had a GM(GMT 50 ) > 450 for BA.4/5 and >1,500 for BA.1 and BA.2. These findings have implications for both CCP stocks collected in prior pandemic periods and for future plans to restart CCP collections. Thus, Vax-CCP provides an effective tool to combat ongoing variants that escape therapeutic monoclonal antibodies. Although COVID-19 convalescent plasma is commonly used for the treatment of immunosuppressed patients, this approach has yielded mixed results. Here, the authors present a systematic review of Omicron-neutralization data in convalescent plasma from vaccinated and unvaccinated individuals.